Meningkatkan Kemampuan Pemecahan Masalah pada Pelajaran Matematika Melalui Strategi Pembelajaran Peningkatan Kemampuan Berfikir pada Siswa Kelas IV Madrasah Ibtidaiyah Al Wathaniyah Tualang Kecamatan Tualang Kabupaten Siak - Hidayatul Alawiyah; Melly Andriani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This research aimed at increasing student problem-solving ability on Mathematics subject through Thinking Skill Enhancementlearning strategy at the fourth grade of Islamic Elementary School of Al WathaniyahTualang, Tualang District, Siak Regency. This research was instigated by the low of student problem-solving ability, it could be seen from 3 of 20 students or 15% showing problem-solving ability that was on good category because many students were not yet able to understand the problems, tocarry out calculations, and to do planning to complete and recheckcalculation results properly. It was a Classroom Action Research. The subjects of this research were a teacher and 20 students atIslamic Elementary School of Al WathaniyahTualang, Tualang District, Siak Regency. Observation, test, and documentation were the techniques of collecting the data. Analyzing the data was done by using qualitative descriptive analysis with percentage. Based on the research finding and data analysis, it showed problem-solving ability that 3 students or 15% were on good category before the action. After implementing Thinking Skill Enhancementlearning strategy in the first cycle, student problem-solving ability increased, 14 students or 70% were on good category. In the second cycle, student problem-solving ability increased, 20 students or 100% were on good category. It meant that it had achieved the successful indicator that was determined. Therefore, it could be concluded that the implementation of Thinking Skill Enhancementlearning strategy could increase student problem-solving ability on Mathematics subjectat the fourth grade of Islamic Elementary School of Al WathaniyahTualang, Tualang District, Siak Regency.